Production of second-generation ethanol from saccharine sorghum bagasse - Vieira, Ana Carolina [UNESP]; Rocha, Ligia Linardi Niero [UNESP]; Chaves, Márcia Rodrigues Morais; Cesarino, Ivana [UNESP]; Leão, Alcides Lopes [UNESP] (Taylor & Francis, 2017)
The sweet sorghum is considered an alternative to complement the sugar cane crop. This study aimed to evaluate the production of 2G ethanol using enzymatic hydrolysis followed by simultaneous fermentation (SSF) compared with the simple fermentation (SHF). The enzymatic hydrolysis used the enzyme complex Accellerase 1500 ® cellulose and for the fermentation was used the yeast Saccharomyces cerevisiae. The obtained yield of ethanol was 96%, where a simple fermentation resulted in lower ethanol content as compared to simultaneous fermentation, 26.8 g/L and 46.6 g/L respectively. Therefore, the sweet sorghum is very promising for 2G ethanol using simultaneous fermentation.
Keywords: Agriwastes; biofuel; biomass; enzymatic hydrolysis; saccharine sorghum; second-generation ethanol